O Direito dos Idosos na União Europeia - Sanja Ivic (Universidade do Estado do Rio de Janeiro, 2013)
Human rights of older adults are still not sufficiently developed. The "older adults" are still perceived as homogeneous social group within legal framework, which leaves room for multiple discrimination. However, the experience of the old age is different and it depends on race, class, gender, occupation, place of living, and so forth. Thispaperwill explorehowthe rights of older adults are regulated within European law. Ageing in Europe is accelerating and puts pressure on welfare systems. That is why both the retirement system and the perception of older adults should be revised. In dealing with the problem of discrimination against older adults, this paper will inquirewhether citizenshipwhich transcends any idea of age represents a symbolic and normative imperative of Europe today.